2010
DOI: 10.1061/(asce)cp.1943-5487.0000018
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Water Distribution Network Design with Honey-Bee Mating Optimization

Abstract: Water distribution network is a costly infrastructure and plays a crucial role in supplying water for the consumers especially for those who are living in the urban areas. The importance and huge capital cost of the system leads to considerable attention on seeking the optimal cost design. The necessity for such a sound research attention arises from the complexity associated with the problem. In the recent years, stochastic optimization algorithms like genetic algorithm, simulated annealing, ant colony optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…These models are mostly based on iterative search algorithms that attempt problem solving with two or more, often conflicting, objective functions. Other techniques have been tested by water supply optimization practitioners and include ant colony optimization [Ostfeld, 2008;L opezeIb añez, 2008], honey bee mating optimization [Mohan, 2009], harmony search [Geem, 2009], tabu search [Cunha, 2004] and shuffled frog leaping optimization [Eusuff, 2003]. A critical review of these methods is presented by S€ orensen [2013], which identifies slight differences in all evolution strategies that are based on the same underlying approach.…”
Section: Optimization Techniques For Ewqmsmentioning
confidence: 99%
“…These models are mostly based on iterative search algorithms that attempt problem solving with two or more, often conflicting, objective functions. Other techniques have been tested by water supply optimization practitioners and include ant colony optimization [Ostfeld, 2008;L opezeIb añez, 2008], honey bee mating optimization [Mohan, 2009], harmony search [Geem, 2009], tabu search [Cunha, 2004] and shuffled frog leaping optimization [Eusuff, 2003]. A critical review of these methods is presented by S€ orensen [2013], which identifies slight differences in all evolution strategies that are based on the same underlying approach.…”
Section: Optimization Techniques For Ewqmsmentioning
confidence: 99%
“…Baños et al [71] also presented a new memetic algorithm and compared its performance on the two-loop, Hanoi and Balerma irrigation networks with several metaheuristic and deterministic optimization methods. Moreover, the scatter search (SS) (aiming at maintaining diverse and high quality solutions) [72], the immune algorithm (IA) (motivated by immunology in protecting the host organism from invaders) [73] and the honeybee mating method (motivated by the biological behavior of honey bees) [74] were also applied to WDN optimization. A comparative study between ACO, IA and SS based on the NYCT network indicated that the ACO always found the global optimum in 20 runs [75].…”
Section: ) Nonpopulation-based Metaheuristicsmentioning
confidence: 99%
“…These algorithms include genetic algorithm [1], simulated annealing [2], tabu search [3], shuffled frog-leaping algorithm [4], ant colony optimization algorithm [5], harmony search [6], cross entropy [7], scatter search [8], hybrid algorithm [9], OPEN ACCESS honey-bee mating optimization [10], differential evolution [11], adaptive cluster covering with local search [12], and Non-Dominated Sorting Genetic Algorithm-II [13].…”
Section: Introductionmentioning
confidence: 99%